Lipid peroxidation of membrane phospholipids in the vertebrate retina - Catala, Angel (2011)
Retina is very rich in membranes containing polyunsaturated fatty acids. Reactive oxygen species initiates chain reactions of lipid peroxidation which injure the retina, especially the membranes that play important roles in visual function. Furthermore, biomolecules such as proteins or amino lipids can be covalently modified by lipid decomposition products. In retinal membranes, peroxidation of lipids is also usually accompanied by oxidation of membrane proteins. In consequence, lipid peroxidation may alter the arrangement of proteins in bilayers and by that interfere with their physiological role on the membrane function. Here, we review several studies on the lipid peroxidation of membrane phospholipids in retina. Particular emphasis is placed on the molecular changes of very long chain polyunsaturated fatty acids associated with protein modifications during peroxidation of photoreceptor membranes. Furthermore we use liposomes to analyze peroxidation of retinal lipids. Conjugated dienes formed from oxidized PUFAs, and TBARS products derived from the breakdown of these fatty acids located in phospholipids can be analyzed during lipid peroxidation of liposomes made of retinal lipids using Fe2+ and Fe3+ as initiators.